The Strategies of Islamic Religious Education (PAI) Teachers in Instilling Noble Character (Akhlak al-Karimah) Among Senior High School (SLTA) Generation Z Students at SMA Darut Taqwa Sengonagung Purwosari - Fitri Handayani, Siti Aisah; Muhammada, Muhammada (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study aims to describe the strategies employed by Islamic Religious Education (PAI) teachers in instilling noble character (akhlak al-karimah) in Generation Z students at SMA Darut Taqwa Sengonagung Purwosari. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving PAI teachers and students. The results indicate that teachers implement several strategies, including role modeling (uswah hasanah), habituation, advice and motivation (mau'izhah hasanah), integration of moral values into various subjects, and the use of digital media. Supporting factors for the success of these strategies include a religious and conducive school environment, support from the school principal and parents, as well as students’ openness to modern approaches. However, several obstacles were also identified, such as the negative influence of social media, inconsistent student behavior outside of school, and a lack of supervision from the family environment. This study highlights that instilling akhlak al-karimah in Generation Z requires a contextual, adaptive approach rooted in Islamic values to address the challenges of the digital era.